A comparative study of smica in various body fluids of diagnosed cervical cancer patients and healthy women - Pooja A. Pachani; Rajendra R. Godbole; Jeevitaa Kshersagar; Rakhi Jagdale; Amita Gosavi; Somshekhar Patil; Rakesh k Sharma; Meghnad G. Joshi (Korean Society of Obstetrics and Gynecology, 2022)
Objective Cervical cancer (CC) is a major public health problem in women, and its early detection can help reduce morbidity and mortality. The objective of this study was to compare serum levels of soluble major histocompatibility complex class I-related chain A (sMICA) levels in various body fluids between women diagnosed with CC and healthy women. Methods A case-control study was conducted at a tertiary care hospital and a cancer center in Kolhapur, India. Overall, 150 individuals (100 CC patients and 50 healthy women) participated after providing informed written consent. Demographic data, histopathology history, parity, and tumor, node, and metastasis (TNM) staging data were collected. Pap smears, saliva, blood, and urine samples were collected. Pap smears were examined microscopically, and sMICA levels in all samples were determined by enzyme-linked immunoassay (ELISA). Results The mean age of women with cervical cancer was 49.86±8.18 years. Squamous cell carcinoma (70%) was the most common histological variant in CC patients. Serum soluble sMICA levels differed significantly with parity and TNM staging (P<0.05). Mean levels of sMICA were significantly different in samples (CC cases vs. healthy patients; saliva: 166.721±108.718 vs. 0.039±0.005 pg/mL; urine: 82.921±45.580 vs. 0.010±0.005 pg/mL; serum: 35.756±10.799 vs. 0.039±0.005 pg/mL, P<0.001). Conclusion Levels of sMICA in body fluids can be considered as a diagnostic or prognostic tool to determine disease progression or tumor regression.